Handbook of research on ePortfolios - Jafari, Ali; Kaufman, Catherine, 1953- (Idea Group Reference, 2006)
"This handbook investigates a variety of ePortfolio uses through case studies, the technology that supports the case studies, and it also explains the conceptual thinking behind current uses as well as potential uses"--Provided by publisher.